Analisis Penyaluran Zakat Mal Di Lembaga Amil Zakat (LAZ): Studi Kasus Insan Madani Provinsi Jambi - Putri Saumilia Lestari; Titin Agustin Nengsih; Solichah Solichah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
Zakat is the fourth pillar of Islam in the form of maliyah ijtima'iyyah worship (economic and social aspects), one of the aims of which is to reduce the economic gap between rich and poor. To fulfill the zakat requirements, there are eight groups called "Mutashiq". Zakat is an asset with certain conditions, Allah SWT requires the owner to hand it over to the person who is entitled to receive it, with certain conditions the property given zakat will be a blessing and will grow and develop, holy and good. Change analysis is defined as a systematic effort to study a research topic by arranging or describing the pieces of information collected into units of analysis. Distribution is the distribution/delivery/distribution of goods and so on to many people or several places. So zakat distribution is the distribution of zakat to people who are entitled to receive it (mustahik zakat) either consumptive or productive. According to the language, zakat mal comes from the word tazkiyah which means to purify property. Meanwhile, according to the term, it is a certain amount of property that Muslims who meet the requirements must give out to people who are entitled to receive it. Mal zakat is also zakat that must be paid if the nisab has been reached (a certain amount).